IMAN YANG ATEIS Konsep Derrida Tentang Iman - Paulus Budi Kleden (STF Driyarkara - Diskursus, 2010)
Abstract: Jacques Derrida is doubtless one of the most controversial phi- losophers of our time. Controversies surrounding him are mainly caused by his radical ideas which have shaken the main traditions of thinking in Western Philosophy. He demonstrates the contradictions of various philophical concepts. He also uses a provocative approach by connect- ing religion with atheism. This essay will demonstrate Derrida’s concept of religion and how it is connected with atheism. Derrida does not present a theology; however his idea of atheistic faith can contribute to a critical understanding of faith and its expressions within religions. Keywords: Iman (faith), agama (religion), teror (terror), ateis (atheist; athe- istic), hadiah (gift; reward), pengetahuan (knowlegde).